Medidas de retrofit em edifícios típicos existentes de um bairro: desempenho e avaliação do ciclo de vida energético - Sartori, Thais Gonçalves (2018)
Many of the environmental impacts from architecture, engineering and construction industry are related to energy consumption, whether from fossil fuels burning or from renewable sources. Buildings consume a significant percentage of the total electric energy generated in Brazil, especially the residential sector. One of the ways to reduce building’s environmental impacts is to increase their energy efficiency, either by adopting more efficient equipment or by improving comfort conditions, implementing techniques and materials more compatible with climate circumstances. One of the goals of retrofit is to increase energy operational and efficiency of existing building. The purpose of the research is to evaluate the influence of retrofit measures on typical dwellings from a neighborhood, both in the envelope performance according to Brazilian Program for Building Labeling and in buildings energy life cycle. Five existing residential buildings typical of Jardim Camburi, a neighborhood located in Vitória, Espírito Santo, were used as the case study. For the envelope performance, the simulation method was used, through EnergyPlus software. The Life Cycle Energy Assessment (LCEA) of the buildings was divided into Embodied Energy and Operational Energy (OE), where the CO2 emissions resulting from this consumption were calculated in addition to the energy consumption. The average carbon emission per unit of energy is 44 Kg CO2/GJ, which is higher in the building that uses gas for water heating. Regarding envelope performance, the most effective measures are those that modify the opaque vertical surfaces, such as absorptance reduction and implementation of ventilated façade. These measures were also the most effective on building’s energy life cycle, with amortization period similar to the average found in similar scientific researches. The green roof proved to be inefficient from the perspective of life cycle energy consumption since it demands more periodic maintenance.